A proposal for the optimization of the geometric configuration of a hollow cylindrical steel damper with slots - Leon, Diego Henao (2023)
The energy dissipation capacity (EDC) of most current configurations of yielding steel dampers is susceptible to be improved by applying optimization concepts. Thus, this study proposes a methodology to enhance the EDC of a slotted hollow cylinder steel (HCS) damper under a cyclic displacement protocol while keeping the same quantity of material via shape optimization. The simulated annealing algorithm was selected for solving the optimization problem as it uses only one candidate solution per iteration, reducing the computational cost associated with the EDC computation. In addition, the finite element software ABAQUS is used to model the behavior of the steel damper under cyclic loads. A code is elaborated using the Python programming language for the optimization process, containing the instructions to be executed in ABAQUS. Five slot configurations were proposed for the initial damper to determine the effect of the initial solution on the optimized HCS damper. The results show that the proposed optimization process obtains optimized models with stable hysteretic behavior and a significantly higher energy dissipation capacity than the initial models. The optimal configuration presented an EDC of 5543 J, 16% higher than the HCS damper without slots and with the same material quantity. The material is mainly located parallel to the beam, simulating two 2D shear steel plates. The difference in EDC with other optimized configurations reaches 955 J, indicating the dependence of the solution on the initial damper configuration. In addition, the difference in the optimized damper topologies proves the multi-modality characteristic of the problem. The proposed algorithm is easy to implement in a computer and reaches the optimal solution with less than 50 iterations.